The study of transparent soap making from virgin coconut oil-based with the addition of white tea extract as an active ingredients - Asri Widyasanti; Anditya Husnul Hasna (Jurnal Penelitian Teh dan Kina, 2016)
Transparent soap was made using high quality materials that beneficial for skin health and beauty. The main ingredient of the transparent soap was virgin coconut oil (VCO), with the addition of white tea extract which was able to increase the benefits of transparent soap. This study aimed to create formulation of the transparent soap, to find the addition of the white tea extracts to produce transparent soap and to study the characteristics of the transparent soap after the addition of white tea extracts. The treatments in this study were the addition of white tea extracts A = 0% (w / w), B = 0.5% (w / w, C = 1.0% (w / w and D = 1.5% (w / w). Observations on the transparent soap were including chemical properties, physical properties of soap, antibacterial and organoleptic test. The results of the analysis showed that all transparent soap formulas met the requirements of solid soap SNI 06-3532-1994, except for the total fatty acid. The formula of transparent soap with treatment B (addition of white tea extract 0.5% w / v) was the best product with organoleptic test results reached 43.34%. The analysis results of those soap were 11.47% of water content and evaporating substances, 37.97% of total fatty acid, 0.519% of free fatty acid, 2.24% of unsaponified fraction, pH value of 9, hardness 0.0077 mm/g/sec, the foam stability of 76.88% and the activity of antibacterial inhibition diameter of 10.7 mm, respectively. This technology could be applied in the production of transparent soap with the addition of white tea extract and to be developed into some industrial scale.